Menteng Atas â Jakarta, Indonesia: A Potrait of Living in Urban Settlement - Sukmajati, Danto (SOSIOHUMANIKA, 2012)
ABSTRACT: Menteng Atas is a sub-district (kelurahan) in Southern Jakarta, Indonesia. As a common crowded settlement in urban area, this location facing multi problems related to social and physical environments. The attempt to adapt and to survive of its various characters and the various origin demography of the community formed this area. This paper explored how members of Menteng Atas community perceive their everyday surroundings within the context of an environment that has rapidly changed, primarily due to urban development, and what they wants for the future of their environment. The study was start from the inside of the local community. A qualitative method with semi grounded research technique had been conducted. Symbolic communication varies from one situation to the next were founded by studying the accounts, explanations, and social action that are meaningful to a group of people. This paper is end up with some recommendations to achieve sustainable housing and settlement at this area. As an urban lower middle class community, they have not self-awareness toward macro scale issues that anytime may affect their area. However, their economic opportunity is good enough both considering the location directly bordered with urban commercial area. An integrated multidimensional planning is needed to upgrade potential environment and community at Menteng Atas that engage all related stakeholders.KEY WORD: Mentang Atas sub-district, urban settlement, built environment, local community, and housing improvement.Â IKHTISAR: Kelurahan Menteng Atas, Jakarta Selatan adalah salah satu contoh permukiman padat perkotaan yang berada di Jakarta. Seperti kawasan padat pada umumnya, daerah Menteng Atas ini menghadapi berbagai permasalahan lingkungan, baik fisik maupun sosial. Kemampuan adaptasi dan survival dari berbagai karakter demografi penduduknya menjadi salah satu pembentuk keunikan kawasan ini. Dalam tulisan ini dieksplorasi bagaimana komunitas warga Menteng Atas menjalani kehidupan kesehariannya dalam batas konteks interaksi dengan lingkungan fisik dan sosialnya, dan apa harapan terhadap masa depan kampungnya. Kajian dijalankan dengan metode kualitatif menggunakan teknik semi âgrounded researchâ. Variasi komunikasi simbolik yang didapat dari satu situasi ke situasi berikutnya dikaji dengan perhitungan, penjelasan, dan tindakan sosial yang bermakna dari kelompok warga. Tulisan ini ditutup dengan beberapa rekomendasi terkait upaya pencapaian lingkungan hunian kota yang berkelanjutan. Sebagai komunitas masyarakat menengah bawah, mereka kurang memiliki kepedulian terhadap lingkungannya. Disisi lain, mereka punya potensi ekonomi terkait kedekatannya dengan sentra komersial kota. Sebuah perencanaan multidimensi yang mampu mengintegrasikan segenap pemangku kepentingan dibutuhkan untuk membuat Menteng Atas menjadi lebih baik.KATA KUNCI: Kelurahan Menteng Atas, permukiman kota, pembangunan lingkungan fisik, komunitas lokal, dan perbaikan kampung.About the Author: Danto Sukmajati is a Lecturer at the Department of Architecture UMB (Mercu Buana University), Jalan Raya Meruya Selatan, Kembangan, Jakarta Barat 11650, Indonesia. For academic purposes, he can be contacted via his e-mail at: dantosukmajati@yahoo.comHow to cite this article? Sukmajati, Danto. (2012). âMenteng Atas â Jakarta, Indonesia: A Potrait of Living in Urban Settlementâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.5, No.2 [November], pp.253-268. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (September 24, 2012); Revised (October 27, 2012); and Published (November 20, 2012). Â  Â